PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, UKURAN DAN KOMPLEKSITAS PERUSAHAAN TERHADAP AUDIT REPORT LAG - Sambuaga, Elfina Astrella; Santoso, Olivia Putri (Ultimaccounting Jurnal Ilmu Akuntansi, 2020)
Abstract- The purpose of this study to examine how agency theory plays a role in determining the factors that affect audit report lag. The difference in outcomes on factors affecting audit report lag in Indonesia and in Malaysia can be due to differences in corporate culture, economic environment, and existing regulations. The test is empirically focused on corporate governance, profitability, firm size and complexity for audit report lag both in Indonesia and Malay. The test uses multiple linear regression method with purposive sampling technique at 308 companies listed on Indonesia Stock Exchange and 361 companies at Bursa Malaysia for the period of 2015. Test results show that profitability called profit or loss of company is the main reason company to immediately publish its financial statement, thus reducing the occurrence of audit report lag. While other factors show different results in both countries. Especially for capital market authorities in Indonesia, it is necessary to consider efforts to improve the timeliness of financial reporting in Indonesia in order to improve the quality of the capital market in order to compete with other developing countries in the ASEAN region. Keywords: agency theory, audit report lag, corporate governance